A design exploration method for resolving parameter coupling in engineering change propagation. (1st January 2011) - Li, Yuliang; Zhao, Wei; Ma, Y-S.
Product design tasks in the upstream and downstream stages are often interdependent in engineering design processes. When design changes propagate from the upstream to the downstream, or vice versa, design tasks in different stages affect each other. Then solving the relevant design problems has to be repeated if the designer cannot find an acceptable solution to satisfy both downstream and upstream design requirements. In this paper, those design task connections with the interdependent nature or phenomena are referred to as design change propagation couplings and the analysis of the coupling is presented. Two types of coupling morphology named concurrent coupling and sequential coupling are identified. A theoretical method as well as a software system to solve such propagation couplings is developed. A design case of the feeding servo system on a numerical controlled machine tool is used to demonstrate the application of the software.